Exploring the Post-secular: the religions, the politics and the urban - Collins, Michael F. (Implicit religion, 2012)
The article reviews the book "Exploring the Post-Secular: The Religions, the Politics and the Urban," edited by A. L. Molendijk, J. Beaumont, and C. Jedan.